NuSTAR and XMM–Newton broad-band spectrum of SAX J1808.4–3658 during its latest outburst in 2015. Issue 1 (3rd November 2018) - Di Salvo, T; Sanna, A; Burderi, L; Papitto, A; Iaria, R; Gambino, A F; Riggio, A
ABSTRACT: The first discovered accreting millisecond pulsar, SAX J1808.4–3658, went into X-ray outburst in 2015 April. We triggered a 100 ks XMM–Newton ToO, taken at the peak of the outburst, and a 55 ks NuSTAR ToO, performed 4 d apart. We report here the results of a detailed spectral analysis of both the XMM–Newton and NuSTAR spectra. While the XMM–Newton spectrum appears much softer than in previous observations, the NuSTAR spectrum confirms the results obtained with XMM–Newton during the 2008 outburst. We find clear evidence of a broad iron line that we interpret as produced by reflection from the inner accretion disc. For the first time, we use a self-consistent reflection model to fit the reflection features in the NuSTAR spectrum; in this case, we find a statistically significant improvement of the fit with respect to a simple Gaussian or diskline model to fit the iron line, implying that the reflection continuum is also significantly detected. Despite the differences evident between the XMM–Newton and NuSTAR spectra, the smearing best-fitting parameters found for these spectra are consistent with each other and are compatible with previous results. In particular, we find an upper limit to the inner disc radius of ∼12 Rg . In all the cases, a high inclination angle (>50°) of the system is required. This inclination angle, combined with measurements of the radial velocity of the optical companion, results in a low value for the neutron star mass (0.8 M_ ), a result that deserves further investigation.